Sepsis: Updates - Noor, Md Mahbub (Pulse, 2022)
Sepsis is a life-threatening organ dysfunction that results from the body's response to infection. To protect against sepsis prompt recognition, careful hemodynamic support, appropriate antibiotics, and control of the source of infection are required. With the trend in management, one should understand sepsis physiology and follow the best practice guidelines. Sepsis and particularly septic shock should be recognized as medical emergency as in stroke and acute myocardial infarction. Early recognition and rapid institution of resuscitative measures are critical. Although recognition of sepsis can be a challenge and the best management practices continue to evolve. This article reviews guidance on the diagnosis and management of sepsis and septic shock with attention to maximizing adherence to best practice and controversies in definition, diagnostic criteria, and management. Pulse volumel.11 January-December 2018-2019 p.7-12